Transposons contribute to the functional diversification of the head, gut, and ovary transcriptomes across Drosophila natural strains - Coronado-Zamora, Marta; González, Josefa (Genome Research, 2023)
Transcriptomes are dynamic, with cells, tissues, and body parts expressing particular sets of transcripts. Transposable elements (TEs) are a known source of transcriptome diversity; however, studies often focus on a particular type of chimeric transcript, analyze single body parts or cell types, or are based on incomplete TE annotations from a single reference genome. In this work, we have implemented a method based on de novo transcriptome assembly that minimizes the potential sources of errors while identifying a comprehensive set of gene–TE chimeras. We applied this method to the head, gut, and ovary dissected from five Drosophila melanogaster natural strains, with individual reference genomes available. We found that ∼19% of body part–specific transcripts are gene–TE chimeras. Overall, chimeric transcripts contribute a mean of 43% to the total gene expression, and they provide protein domains for DNA binding, catalytic activity, and DNA polymerase activity. Our comprehensive data set is a rich resource for follow-up analysis. Moreover, because TEs are present in virtually all species sequenced to date, their role in spatially restricted transcript expression is likely not exclusive to the species analyzed in this work.
10.1101/gr.277565.122